Akuntansi Dalam Pencapaian Tujuan Rumah Tangga Islami - Dwiya Endah Pandu Probowati (Ecopreneur : Journal of Sharia Economics Study Program, 2021)
As stated by Allah in Surah Al Baqarah 282, Islam views accounting as a mandate that must be carried out in muamalah activities. From a scientific point of view, accounting is a science, art and technique of financial recording of business entities which includes the process of recording, journaling, and reporting. In a business entity, accounting is a tool that can help achieve the goals of a business entity, namely profit, accounting provides financial report output that can be a source of information related to the performance of business entity managers, seeing profitability and business performance trends from period to period and so on. In general, the use of accounting will simplify the accountability process, assist in performance appraisal and facilitate the achievement of business entity objectives. The household is the smallest social entity that has a goal, in Islam the goal of the household is to achieve sakinah mawaddah and wa rokhmah, in order to achieve this goal, special well-planned steps are needed. In household accounting plays a very important role in the process of recognizing what household resources are, budgeting household needs both in the short and long term, further accounting also helps implementers of household activities to see the realization and household budgets. This research is a qualitative research using library research method. In this study, the researcher revealed the important role of accounting for the achievement of household goals in an Islamic economic perspective. The purpose of this study is to provide an understanding of "the importance of accounting in household management, so that the objectives of the Islamic household of Sakinah Mawaddah Warokhmah can be achieved." Abstrak Sebagaimana dinyatakan Allah dalam Surah Al Baqarah 282, Islam memandang akuntansi sebagai amanah yang harus dijalankan dalam kegiatan muamalah. Dari sudut pandang keilmuan, akuntansi adalah ilmu, seni dan teknik pencatatan keuangan badan usaha yang meliputi proses pencatatan, penjurnalan, dan pelaporan. Dalam suatu badan usaha, akuntansi merupakan suatu alat yang dapat membantu mencapai tujuan suatu badan usaha yaitu laba, akuntansi memberikan keluaran laporan keuangan yang dapat menjadi sumber informasi yang berkaitan dengan kinerja pengelola badan usaha, melihat profitabilitas dan trend kinerja usaha. dari masa ke masa dan seterusnya. Secara umum penggunaan akuntansi akan mempermudah proses pertanggungjawaban, membantu dalam penilaian kinerja dan memudahkan pencapaian tujuan badan usaha. Rumah tangga adalah entitas sosial terkecil yang mempunyai tujuan, dalam Islam tujuan rumah tangga adalah mencapai sakinah mawaddah dan wa rokhmah, untuk mencapai tujuan tersebut diperlukan langkah-langkah khusus yang terencana dengan baik. Dalam akuntansi rumah tangga memegang peranan yang sangat penting dalam proses pengenalan apa itu sumber daya rumah tangga, penyusunan anggaran kebutuhan rumah tangga baik dalam jangka pendek maupun jangka panjang, selanjutnya akuntansi juga membantu pelaksana kegiatan rumah tangga untuk melihat realisasi dan anggaran rumah tangga. Penelitian ini merupakan penelitian kualitatif dengan metode penelitian kepustakaan. Dalam penelitian ini, peneliti mengungkapkan peran penting akuntansi untuk pencapaian tujuan rumah tangga dalam perspektif ekonomi Islam. Tujuan dari penelitian ini adalah untuk memberikan pemahaman tentang â€œpentingnya akuntansi dalam pengelolaan rumah tangga, sehingga tujuan rumah tangga islami Sakinah Mawaddah Warokhmah dapat tercapaiâ€.